Importance of targeted next-generation sequencing in pediatric patients with developmental epileptic encephalopathy - Bari, Savas; Kirik, Serkan; Balasar, Ozgur (Assoc Medica Brasileira, 2023)
OBJECTIVE: Childhood epilepsy is a common neurological disorder with a prevalence of 300-600 cases per 100,000 people. It is associated with refractory epilepsies, global developmental delay, and epileptic encephalopathies, causing epileptic syndromes characterized by cognitive and behavioral disorders. METHODS: In this retrospective cohort study, patients with refractory epilepsy and global developmental delay, defined as epileptic encephalopathy, who applied to the Aydin 7Maternity and Children's Hospital Genetic Diagnosis Center and were followed in the pediatric neurology clinic of our hospital, between July 2018 and July 2021, were included. RESULTS:Targeted next-generation sequencing molecular genetics results were reviewed, and 3 ALDH7A1, 1 AARS, 3 CACNA1A, 1 CTNNB1, 1 DCX, 2 DBH, 2 DOCK7, 1 FOLR1, 2 GABRB3, 2 GCH1, 1 VGRIN2B, 1 GUF1, 3 KCNQ2, 2 KCNT1, 1 NECAP1, 1 PCDH19, 1 PNPO, 1 SCN8A, 1 SCN9A, 4 SCN1A, 2 SLC25A22, 1 SLC2A1, 2 SPTAN1, 2 SZT2, 4 TBC1D24, 2 TH, and 1 PCDH19 (X chromosome) mutations were detected in three of the patients using the next-generation sequencing method. CONCLUSION: Although the development of gene panels aids in diagnosis, there are still unidentified disorders in this illness category, which is highly variable in genotype and phenotype. Understanding the genetic etiology is vital for genetic counseling and, maybe, the future development of remedies for the etiology.
Keywords: Epilepsy; Neurological disorder; Pediatrics; Next-generation sequencing